Hybrid Cu-to-Cu bonding with nano-twinned Cu and non-conductive paste - Yu-Hao Kuo; Dinh-Phuc Tran; Jia-Juen Ong; K.N. Tu; Chih Chen (Journal of Materials Research and Technology, 2022)
Highly (111)-oriented nanotwinned copper (nt-Cu) and non-conductive paste (NCP) were employed to fabricate hybrid Cu–Cu bonding. We tailored and correlated the fracture modes, bonding strengths, and microstructures of the joints. A non-flow underfilling process was performed, and low temperature bonding was achieved in a single heat treatment at 180 °C for 120 min without vacuum. We found that under a post-annealing treatment, recrystallization and grain growth occurred. The bonding interfaces were partially removed and the joints were further strengthened. The fracture modes of the hybrid bonding structure were characterized using pull tests and correlated with their bonding properties. Such hybrid Cu–Cu microbumps with high bonding strength and low thermal budget can be widely used for advanced ultra-fine-pitch packaging.